Developing STEM integrated analysis geometry learning materials through digital visualization and e-learning platforms - Fitriawan, Dona; Siregar, Nurfadilah; Hartoyo, Agung; Sulistyowati, Endar (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: This study aims to develop STEM-based Analytical Geometry teaching materials integrated with digital visualization tools and e-learning platforms. The goal is to enhance students’ conceptual understanding, spatial visualization, and problem-solving skills while addressing the limitations of traditional instruction, particularly in connecting abstract concepts to real-world applications. Method: A research and development approach was employed using the ADDIE model (analysis, design, development, implementation, and evaluation). The study involved 93 fifth-semester undergraduate mathematics education students. Data were gathered through observations, interviews, needs analysis questionnaires, expert validation, learning outcome tests, and student feedback. The teaching materials included various digital tools such as GeoGebra, PhET, Maple, Tinkercad, and Google Colab, supporting STEM-based learning and engineering projects. Quantitative data were analyzed using descriptive statistics and gain score analysis, while qualitative data were used to interpret the implementation process. Findings: The developed materials achieved a high validity score (4.58/5). The implementation through e-learning led to a 36.6% improvement in student learning outcomes. Student feedback was overwhelmingly positive, with a score of 4.63, particularly in visual clarity and ease of use. Engineering projects, such as robot path design, enhanced students’ spatial reasoning and facilitated concept transfer. Significance:This study provides evidence that integrating STEM, digital visualization, and e-learning significantly enhances the effectiveness of analytical geometry learning, offering practical implications for innovative mathematics education technologies aligned with Industry 4.0 and Society 5.0.